An Analysis Of Cohesion Found In The Main ArticlesIn The Asia 360 News Magazine - Lestiani, Atmi (2012)
The study is about describing cohesion found in the main articles in the Asia 360 News Magazine. The objective of this research are to describe the lexical cohesion and grammatical cohesion in the main articles in the Asia 360 News Magazine. This research is a descriptive qualitative study which analyzes the elements of cohesions of the main articles. The data are sentences which include the lexiical and grammatical cohesions found on the main article in the Asia News 360 Magazine. The researcher collects the data by reading the articles, coding, making list on lexical and grammatical cohesion in the articles, and describing the lexical and grammatical cohesions toward Main Articles in the Asia News 360 Magazine based on Halliday and Hasan's theory. The result shows that the cohesive devices in the Main Articlesinclude the grammatical and lexical cohesions. The grammatical cohesions consists of reference: (1) personal reference 27,39% and demonstrative reference 4,56%, (2) conjunction; coordinating conjunction 24,56%, subordinating conjunction 21,74% and correlation conjunction 0,22%, (3) Ellipsis 6,52% and (4) substitution 3,26% while the lexical cohesions consists of (1) Repetition 8,26%, antonym 0,87%, synonym 2,39%, and hyponym 0,22%. In the articles, the use of grammatical cohesions are higher than the lexical cohesions.